Experimental Research in Audiovisual Translation – Cognition, Reception, Production - Diaz Cintas, Jorge; Szarkowska, Agnieszka (The Journal of Specialised Translation, 2020)
In recent years, an unprecedented boom in experimental research conducted in the field of audiovisual translation (AVT) has taken place, marking a shift from individual, descriptive case studies towards an attempt at establishing some evidence-based truths. Using a combination of new methods and technologies, AVT researchers have embarked on the examination of various cognitive aspects governing not only the reception of translated audiovisual programmes but also the actual translation process behind practices like subtitling, captioning, dubbing, voice-over and audio description. This special issue aims to reflect this new trend, by capturing both research strands: reception and production. The paper starts with a discussion of the experimental and cognitive research shift in AVT studies, stressing the special, multimodal nature of audiovisual communication. A higher rate of replication and reproducibility of AVT research is also postulated, with suggestions of how to promote this. Finally, a summary of the contents of this special issue is presented, structured in three main parts: (1) conducting experimental research with the help of biosensor devices, (2) researching the behaviour of AVT professionals and (3) carrying out survey-based reception studies.